PERLINDUNGAN HUKUM TERHADAP PELANGGARAN HAK CIPTA MELALUI MEDIA INTERNET BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Andrew Shandy Utama; Sandra Dewi; Bagio Kadaryanto (Jurnal Ilmu Hukum, 2018)
Initially the scope of copyright protection only focused on conventional objects of creation. However, along with technological developments and advances, the object of copyright protection is expanding on the forms of creation in the form of science, art, and literature are digitized. Copyright Laws that are currently still experiencing some problems in order to provide protection to the creative works expressed through the internet media. Therefore, it is interesting to examine the legal protection against copyright infringement through internet media based on Law Number 28 Year 2014. The method used in this research is normative legal research. Sources of data used in this research are secondary data, namely data obtained from legislation, scientific journals, and legal literature. Data collection techniques used in this research is literature study. Data analysis technique used in this research is qualitative analysis. The results of this research indicate that the development and advancement of technology increasingly facilitate the occurrence of violations of Copyright through the internet media are hijacked, copied, and traded in the midst of society. Although in Law Number 28 Year 2014 has been set about bans and strict criminal sanctions, but due to weak regulation and lack of legal awareness of the public make law enforcement of Copyright is not running optimally.